Multinationals as Arbitrageurs: The Effect of Stock Market Valuations on Foreign Direct Investment - Baker, Malcolm; Foley, C. Fritz; Wurgler, Jeffrey (Review of Financial Studies, 2009)
[Empirical evidence of imperfect integration across world capital markets suggests a role for cross-border arbitrage by multinationals. Consistent with multinational arbitrage as a determinant of foreign direct investment (FDI) patterns, we find that FDI flows increase sharply with source-country stock market valuations–particularly the component of valuations that is predicted to revert the next year, and particularly in the presence of capital account restrictions that limit other mechanisms of cross-country arbitrage. The results suggest the existence of a cheap financial capital channel in which FDI flows reflect, in part, the use of relatively low-cost capital available to overvalued parents in the source country.]